Scalar fields as dark matter candidates in the modified left-right symmetry model - Istikomah, Istikomah; Isnawati, Nurul Embun (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2023)
Dark matter is about 25% of the universe, but its existence is still a mystery. The Modified Left-Right Symmetry Model with the extension of the scalar field, is expected to explain dark matter candidate. The dark matter candidates were analyzed using the Higgs Potential and Lagrangian Yukawa to obtain information on decay and scattering interactions. The generation of dark matter can be determined by analyzing the temperature evolution of the universe, which is divided into three stages post-inflation reheating, symmetry breaking first step, and symmetry breaking second step. The analysis results show that the right-sector scalar field can be Cold Dark Matter (CDM) candidate because it has non-relativistic characteristics, is stable, does not interact with fermions, and has an abundance of 0.004. The right-sector atom can also be a CDM candidate because it has non-relativistic characteristics, is neutral, and consists of the right nucleons and right electrons. The singlet scalar field can be the Warm Dark Matter (WDM) candidate because it can decay into fermion, interact in the left and right sectors, is neutrally charged and does not interact with other particles electromagnetically and has an abundance of 0.003. Thus, based on the modified left-right symmetry model, the particle that can be a candidate for dark matter is the scalar field.